2021
DOI: 10.1098/rspb.2020.2840
|View full text |Cite
|
Sign up to set email alerts
|

Predation favours Bicyclus anynana butterflies with fewer forewing eyespots

Abstract: There are fewer eyespots on the forewings versus hindwings of nymphalids but the reasons for this uneven distribution remain unclear. One possibility is that, in many butterflies, the hindwing covers part of the ventral forewing at rest and there are fewer forewing sectors to display eyespots (covered eyespots are not continuously visible and are less likely to be under positive selection). A second explanation is that having fewer forewing eyespots confers a selective advantage against predators. We analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
(63 reference statements)
3
5
0
Order By: Relevance
“…This is consistent with the hypothesis, derived from the tropical butterfly Bicyclus anynana (Lyytinen et al, 2004), that predation maintains eyespot plasticity. It is also consistent with the idea that ‘covered’ eyespots, which are not continuously visible to predators, are less likely to be under positive selection (Chan et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with the hypothesis, derived from the tropical butterfly Bicyclus anynana (Lyytinen et al, 2004), that predation maintains eyespot plasticity. It is also consistent with the idea that ‘covered’ eyespots, which are not continuously visible to predators, are less likely to be under positive selection (Chan et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Whereas more forewing spots produce less symmetrical damage in males but more asymmetrical damage in females, intriguingly suggesting that they may have opposite effects in different sexes. A similar relationship between forewing spotting and survival has been noted in B. anynana where predation experiments have confirmed that female butterflies with fewer forewing spots live longer and lay more eggs (Chan et al, 2021). Given that the number of hindwing spots in both sexes of M. jurtina declines strongly across the season, this suggests that any role in predator deflection will also be decreased over time.…”
Section: Discussionsupporting
confidence: 64%
“…Butterfly wings exhibit an astounding diversity of patterns shaped by their roles in thermoregulation [ 1 , 2 ], mate choice [ 3 5 ], and predator deterrence [ 6 8 ]. Of these wing patterns, eyespots, with their concentric rings of contrasting colours, are arguably one of the most well-studied patterns for their ecological functional roles in predator avoidance and in mate signalling [ 9 15 ]. It is also interesting that simpler traits, such as spots in pierid and lycaenid butterflies [ 5 , 16 ], have also been implicated in mate signalling, but the developmental similarities and evolutionary relationship between spots and eyespots have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In butterflies, wing margins displaying eyespots are preferentially attacked (e.g. in Bicyclus anynana [14], in Lopinga achine [15]). The loss of wing margins and especially hindwing margins has a low impact on butterflies flying abilities [16] and may therefore have a limited impact on survival.…”
Section: Introductionmentioning
confidence: 99%